131I-Orthoiodohippurate Clearance in the Detection of Cisplatin Nephrotoxicity - Hengst, w.; wieier, H.; Rabs, u.; Bürger, A.R. (Nuklearmedizin - NuclearMedicine, 1985)
In this study, 26 patients were treated with 20 mg cisplatin (CP)/m2 body surface daily for 5 days as part of a combination therapy for testicular cancer. Simultaneously a vigorous hyperhydration (3000 ml daily) was applied to reduce the nephrotoxic effect induced by the drug, 131I-orthoiodohippurate clearance values obtained by the modified method of Oberhausen did not show any significant evidence of tubular dysfunction after therapy. These results may have been due to the vigorous hydration as well as to the youth of the patients.